The impact of COVID-19 restrictions on perceived health and wellbeing of adult Australian sport and physical activity participants - R. Eime; J. Harvey; M. Charity; S. Elliott; M. Drummond; A. Pankowiak; H. Westerbeek (BMC, 2022)
Abstract Individuals' access to sport and physical activity has been hampered due to COVID-19 lockdown restrictions. In Australia participation in community sport was cancelled during lockdowns. There is limited research on the impact of sport participation restrictions on the health and wellbeing of adults. Aim The aim of this study was to investigate the perceived health and wellbeing of a sample of predominantly active Australian adults, both during COVID-19 and in comparison with one year earlier (pre COVID-19). Methods A survey was conducted during the first COVID-19 restrictions and lockdowns in Australia in May-June 2020. It was distributed by national and state sporting organisations and through researchers' social media accounts. This particular paper focuses on adults aged 18-59 years. The survey collected information on participant demographics, the sport and physical activity patterns pre- COVID-19, and health and wellbeing outcomes during COVID-19 lockdown and compared to one year earlier. The health measures were cross-tabulated against the demographic and sport and physical activity variables, and group profiles compared with chi-square tests. Scales were derived from three wellbeing questions, and group differences were analysed by t-tests and F-tests. Results The survey sample included 1279 men and 868 women aged 18-59 years. Most (67%) resided in metropolitan cities. The great majority (83%) were sport participants. During COVID-19 lockdown men were significantly more likely than women to report worse or much worse general (p = 0.014), physical (p = 0.015) and mental health (p = 0.038) and lower life satisfaction (p = 0.016). The inactive adults were significantly more likely to report poorer general health (p = 0.001) and physical health (p = 0.001) compared to active adults. The younger age cohort (18-29 years) were significantly more likely to report poorer general wellbeing (p < 0.001), and lower life satisfaction (p < 0.001) compared to the older age groups. Conclusion It seems that the absence of playing competitive sport and training with friends, teams and within clubs has severely impacted males and younger adults in particular. Sports clubs provide an important setting for individuals' health and wellbeing which is why clubs require the capacity to deliver sport and individuals may need to regain the motivation to return.